Comparative Analysis of Financial Performance Using Financial Ratios and Economic Value Added - Karim, Kurniati (International Journal of Indonesian Business Review, 2022)
This study aims to determine 1) monitor the financial performance of PT. Indofood Sukses Makmur Tbk. based on Financial Ratios 2) financial performance of PT. Indofood Sukses Makmur Tbk. based on Economic Value Added (EVA) 3) calculated based on the financial performance of PT. Indofood Sukses Makmur Tbk. based on Financial Ratios and EVA. Results Based on the research shows that the liquidity ratio is measured using the Current Ratio (CR). the average CR was 159% or 1.59 times, indicating that the company cannot afford the short term or the debt is due soon. The solvency ratio is measured using the Debt to Equity Ratio (DER) the average DER is 92.72%, indicating that the company uses other parties' capital more than its own capital. Activity Ratio is measured using TATO. TATO obtained an average of 74% or 0.74 times indicating ineffective asset turnover or the company has not maximized assets in generating sales. Profitability ratios are measured using ROE.  ROE of 11.48% was obtained, indicating that the company does not yet have equity in obtaining company profits or profits. Meanwhile, by using the EVAmethod, the average EVA is 1,288,895 which shows positive results or EVA > 0. From the results of this explanation it can be said that the measurement of financial performance is better using the EVA method.